Penyusunan laporan keuangan UMKM berdasarkan SAK EMKM pada UMKM CV. Talida Citra Swara - Bayu Swargi; Wulan Dri Puspita (University of Merdeka Malang, 2023)
This research was conducted on CV. Talida Citra Swara which is one of the SMEs in the city of Malang. This study aims to determine financial management based on Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM) in SMEs CV. Talida Citra Swara. The type of research used in this research is a qualitative approach. The results of this study indicate that the understanding of business owners regarding financial management based on SAK EMKM is still low, and there is no financial record so that the owner cannot know the income earned. Preparation of Financial Statements Based on SAK EMKM on CV. Talida Citra Swara will have a positive impact on MSMEs, with the preparation of Financial Statements based on SAK EMKM, business owners can manage their business finances better.